Phytochemical Screening of Ethanol Extracts from Three Variants of Kratom Leaves (Mitragyna speciosa Korth.) - Masriani Masriani; Rini Muharini; Dinda Kartika Wijayanti; Purnama Melanie; Margareta Lita Widiansari (Universitas Pendidikan Mandalika, 2023)
Kratom (Mitragyna speciosa Korth.) has been traditionally used in the community for medicinal purposes. Kratom leaves have been reported to possess various biological activities such as antioxidant, antibacterial, anti-inflammatory, and antinociceptive effects. The biological activity of kratom leaves is believed to be attributed to the presence of secondary metabolites. The aim of this study was to investigate the content of secondary metabolite compounds in three types of kratom leaves, namely green, red, and white kratom. Each 200 g of kratom leaf powder was subjected to 72 hours of maceration with 1 L of 96% ethanol solvent. The resulting extract was filtered and concentrated using a water bath and an oven at a temperature of 50oC to obtain a concentrated extract. The extract was evaluated for its yield and secondary metabolite content using specific reagents for each test. The results revealed the presence of secondary metabolites such as alkaloids, flavonoids, triterpenoids, phenolics, tannins, and saponins in the red, green, and white kratom leaves. These findings provide a valuable reference for future bioactivity research and identification of the bioactive compounds present in the three variants of kratom leaves.